Analisis Sumber Daya Perusahaan Dan Lingkungan Eksternal: Studi Kasus pada Industri Kreatif Digital Pasca Pandemik Covid 19 - Ermaya, Sir Kalifatullah; Mulyana, Iwan; Nur Laela Ermaya, Husnah; ARR, Tryiis (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This research highlights company resource variables and the external environment in the digital creative industry in West Java, which is registered with Aspiluki. There were 25 respondents in this study, consisting of owners and managers. This research uses quantitative and descriptive research methodologies. Company resources are everything that the company owns and can control. Meanwhile, the external environment is the environment outside the organization that can influence a company. The results show that the biggest indicator of the company resource variable is